Efecto de densidades de siembra en el cultivo de cebolla perla (Allium cepa L.) en Ecuador - Muguerza De La Cruz., Susan María (2021)
This collection of information refers to the effect of planting densities in the pearl onion (Allium cepa L.) crop in Ecuador. Within the agronomic management of the pearl onion crop, many factors that influence the yield stand out and that begin from the preparation of the seedbed to the harvest, within which there are sowing densities, attack by pests and diseases, nutritional deficiencies, irrigation and weed control. Among the conclusions, it is detailed that the area with the highest pearl onion production in Ecuador corresponds to the province of Chimborazo, with approx. 45000 tons per year; the increase in plant density advances the maturity date, increases the percentage of intercepted radiation and the total yield of bulbs and reduces the number of green leaves, number of rings and size of the bulbs; The response to the sowing distance depends mainly on the following factors: type of crop, characteristics of the genotype, sowing method, environmental conditions of the region (climate and soil), purpose of the crop, economic efficiency and the irrigation system and use a planting density of 44 plants / m2 because with this density the best yields and the highest benefit / cost ratio are obtained.